“Fearless” Revisited: How This Peer-to-Peer Self-Help Group for Sex Offense Registrants and Their Families Continued to Operate during a Global Pandemic - Sample, Lisa L. (International journal of offender therapy and comparative criminology, 2025)
Among the challenges of the COVID-19 pandemic, peer-to-peer support groups sought virtual environments to bring individuals together. Building upon previous research of Fearless, a peer-to-peer support group for registered individuals, this study examines how changes in the format from in person to virtual impacted the group’s ability to provide social support to members. A snowball sampling technique was used to identify 25 members of Fearless who regularly attended the group’s virtual monthly meetings during the COVID social restrictions. Using thematic narrative analysis, researchers found that the virtual format offered both positive and negative changes for members of the group. Although participants note various challenges of virtual meetings, like concerns for privacy, online meetings still provided opportunities for members to continue identity work, which is critical for continued prosocial behavior.